A comparative study of the major glycoprotein isolated from normal and neoplastic gastric mucosa. Issue 4 (April 1973) - Schrager, J.; Oates, M. D. G.
Abstract : The isolation and composition of glycoproteins from mucosae of normal stomachs, of stomachs with gastric ulcer, and of stomachs with carcinoma is described. The glycoproteins from the mucosae of normal stomachs and with gastric ulcer showed virtually the same carbohydrate and amino acid content as the principal gastric glycoprotein isolated from gastric aspirates. They all revealed a common basic carbohydrate composition: galactose, fucose, glucosamine, and galactosamine were present in approximate molar ratios of 4:3:3:1. The results suggest that the glycoproteins isolated from gastric aspirates from normal and neoplastic gastric mucosae share a number of structural features: (1) a protein core with a characteristic amino acid composition; (2) the range of sugars forming the carbohydrate side chains; (3) galactosamine approximately equimolar with the sum of threonine and serine; (4) galactose approximately equimolar with the sum of glucosamine and galactosamine; (5) absence of mannose; (6) a high carbohydrate content (80-85%); and (7) blood group activity. The neoplastic glycoproteins differed from the normal glycoproteins in that the quantitative relationships of the carbohydrate components of the neoplastic glycoproteins showed variations dividing the extracts investigated into groups, each group with a distinctive and constant carbohydrate composition. The blood group specificity of 15 out of 24 cases investigated differed from that of the hosts' red cells.